Effects of Young Barley Leaf Powder on Gastrointestinal Functions in Rats and Its Efficacy-Related Physicochemical Properties. (8th July 2014) - Ikeguchi, Motoya; Tsubata, Masahito; Takano, Akira; Kamiya, Tomoyasu; Takagaki, Kinya; Ito, Hideyuki; Sugawa-Katayama, Yohko; Tsuji, Hideaki
Abstract : Young barley leaf is consumed as a popular green-colored drink, which is named "Aojiru" in Japan. In the present study, we examined effects of young barley leaf powder (BL) on gastrointestinal transit time (GTT) and fecal moisture and weight in comparison with wheat bran (WB) in male Sprague-Dawley rats. In addition, an attempt was made to identify BL components responsible for these effects by using various fractions of BL. Additionally, we examined the water-holding capacity and setting volume of BL in vitro . We also examined the granular structures of BL with a scanning electron microscope. As a result, BL supplementation in the diet increased the fecal weight and shortened GTT. Our results demonstrate that the active component responsible for the effect on increasing the fecal volume in BL is the water-insoluble dietary fiber fraction and that this effect is thought to be caused by stimulation of the gut tract by the pH lowering. Furthermore, the high laxative action of BL was thought to be ascribable to the high water-holding capacity due to the complicated structures of BL.